The congenital long QT syndrome and implications for young athletes - Kapitanoupolos, A.; Kluger, J.; Maron, B. J.; Thompson, P. D. (Medicine & Science in Sports & Exercise, 2006)
The congenital long QT syndrome (LQTS) is caused by cardiac ion channel mutations, which predispose young individuals to sudden cardiac death often related to exercise. The issue of LQTS and sports participation has received significant publicity due to reports of sudden death in young competitive athletes. This article reviews the pathophysiology, clinical characteristics, and management of LQTS in the physically active and athletic population.